Fermented milk-based baby drinks fortified by prebiotics and probiotics: impact on the health of infants and young children - I.N. Zakharova; I.V. Berezhnaya; E.V. Skorobogatova (LCC «Medicine-Inform», 2022)
I.N. Zakharova1,2, I.V. Berezhnaya1,2, E.V. Skorobogatova2 1Russian Medical Academyof Continuous Professional Education of the Ministry of Health of the Russian Federation, Moscow, Russian Federation 2Z.A. Bashlyaeva Children's City Clinical Hospital, Moscow, Russian Federation Nowadays, rational, balanced nutrition and fortified foods are becoming increasingly popular among physicians of different specialties who have medical practice settings throughout the world. Even earlier, these food shave been recommended for the prevention of multiple disorders, including such socially significant diseases as myocardial infarction, diabetes mellitus, obesity, cancer, and allergy. Trends of the past few decades have demonstrated that functional nutrition will provide most benefits if it is started from early childhood. As elsewhere in the world, novel probiotics are regularly developed in Russia as targeted therapies. The use of fermented milk-based products fortified by probiotics like S. Thermophilus FD DVS nutrish® La-5® (Lactobacillus acidophilus), Bifidobacterium animalis subsp. lactis ВВ-12 in baby formulae helps to achieve a balanced diet, develop positive nutritional behavior and to reduce the rate and severity of infectious and allergic diseases in children. The National program for optimizing nutrition of children in the Russian Federation serves as guide for doctors and parents allowing them to select the best products available on the market of commercially produced foods for infants and children. The article provides a definition of functional nutrition and characteristics of fermented foods in children's diet. It also describes effects of various probiotic strains in the line of functional baby food. Keywords: probiotics, S. Thermophilus, Lactobacillus acidophilus, functional baby food, fermented milk products for complementary feeding, biolact. For citation: Zakharova I.N., Berezhnaya I.V., Skorobogatova E.V. Fermented milk-based baby drinks fortified by prebiotics and probiotics: impact on the health of infants and young children. Russian Journal of Woman and Child Health. 2022;5(3):253-261 (in Russ.). DOI: 10.32364/2618-8430-2022-5-3-253-261.